2022
DOI: 10.3390/su141710780
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Effective Thermal Performance of Street Canyons in Various Climatic Zones

Abstract: Outdoor thermal comfort is one of the essential characteristics of effective urban planning. The aspect ratio and orientation of the street canyon influence the thermal performance. Regulations standardize construction rules without accounting for regional climatic variations or the effect of these limits on pedestrian thermal comfort. The purpose of this paper is to provide an understanding of the effects of aspect ratios and street canyon orientations on thermal comfort in Alexandria, representing the North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Similarly, the increase in building height, which also leads to an increase in the aspect ratio, leads to a reduction of the sky-view factor, augments the proportion of shadowed areas on the ground, and therefore reduces the heat stress in summer. Similar observations have been made in some studies, which also concluded that deep street canyons (with a high aspect ratio) are beneficial to pedestrian thermal comfort [67].…”
Section: Impact Of Individual Morphology Indicators On Outdoor Therma...supporting
confidence: 89%
“…Similarly, the increase in building height, which also leads to an increase in the aspect ratio, leads to a reduction of the sky-view factor, augments the proportion of shadowed areas on the ground, and therefore reduces the heat stress in summer. Similar observations have been made in some studies, which also concluded that deep street canyons (with a high aspect ratio) are beneficial to pedestrian thermal comfort [67].…”
Section: Impact Of Individual Morphology Indicators On Outdoor Therma...supporting
confidence: 89%
“…Recently, more emphasis has been placed on understanding the relationship between urban features and local climate and devising mitigation and adaptation techniques to enhance urban thermal performance [7,8]. Several studies on the effects of various urban geometrical thermal mitigation measures on outdoor spaces have been conducted for hot, arid climate zones [9][10][11][12].…”
Section: Of 23mentioning
confidence: 99%
“…An important aspect of a passively designed building envelope is the reduced energy needed to maintain a comfortable inside temperature [6,16,21]. This method takes into account the heat gain from the outside, which is affected by the building's walls, fenestration, roof [38], foundation, thermal insulation [26,27], thermal mass [39], and external shading systems [40][41][42], into consideration [16,43]. Regardless of the ever-changing weather outside, this crucial aspect is what ultimately decides the quality of the structure and what governs the internal conditions [16,21,43,44].…”
Section: Investigating Energy Efficiency In Buildingsmentioning
confidence: 99%